ByzRev 05.2023.013: Mischa Meier – Federico Montinaro (eds), A Companion to Procopius of Caesarea: (Brill’s Companions to the Byzantine World 11). Leiden – Boston: Brill 2022. - Signes Codoñer, Juan (The Byzantine Review, 2023)
Mischa Meier – Federico Montinaro (eds), A Companion to Procopius of Caesarea (Brill’s Companions to the Byzantine World 11). Leiden – Boston: Brill 2022. 474 pp. – ISSN 2212-7429 / ISBN 978-90-04-49876-1